Analyzing the Feedback from Women Dairy Farmers in the East District of Sikkim - Lepcha, Chimi Yangzom; Asif Mohammad; Waris Ali (Indian Journal of Extension Education, 2023)
The dairy sector is a women-centric endeavor. It is an instrument for elevating the vulnerable section of society, particularly the farm women. Farm women contribute diligently towards dairy activities. The study was conducted in the East district of Sikkim in the year 2021. A simple random technique was used for selecting four blocks, five villages from each block, and ten respondents from each village were randomly selected. A personal interview schedule was used for the collection of data. Data were collected from 200 dairy farm women owning at least one dairy cattle. The study analyzes the feedback of dairy farm women based on five aspects, i.e., economical, technical, administrative, information networking, and independent decision-making. The result revealed that the high cost of concentrate, feed, and fodder, delayed service of animal health officials, lack of financial support from the government, irregular information on government schemes on dairy, and non-availability of financial support to women farmers were some of the major feedbacks given by the respondents.